Measuring bullying at work with the short-negative acts questionnaire: identification of targets and criterion validity - Notelaers, Guy; Van der Heijden, Beatrice; Hoel, Helge; Einarsen, Ståle (Work and stress, 2019)
The current study aims to investigate the psychometric properties of the abbreviated version of the Negative Acts Questionnaire, also known as the SNAQ (Short Negative Acts Questionnaire). A Latent Class analysis of 7,790 observation from 38 Belgian organizations demonstrated that four latent classes of respondents can be distinguished in our data: 'not bullied', 'work-related criticism', 'occasionally bullied', and 'severe targets'. Like with the original full version, both occasionally bullied and the severe targets align with the theoretical definition of workplace bullying as exposure to repeated and systematic negative behavior. The extent to which these clusters report bullying does not only account for their difference, yet also the type of behavior sets the two categories apart. Whereas severe targets had a high probability to report social isolation, this type of social behaviors was more likely to be absent among the occasionally bullied group. The results from the HSD post-hoc test demonstrated that both occasionally bullied and severe targets experienced deteriorating health, more sickness absenteeism and lower for job satisfaction than the two other latent class clusters. Hence, the SNAQ seems to be a psychometrically sound and easy to use instrument to identify targets exposed to varying degrees of workplace bullying.